A Short History of the Development of Hospital Pharmacy in Belgium - Jean-Daniel Hecq (MDPI AG, 2016)
The Belgian Association of Hospital Pharmacists (BAHP) is a professional and scientific association representing all pharmacists who work in hospital institutions, whether private or public, university, general or psychiatric. This association was created in 1953. The aim of this short paper is to tell the history of its continuous development in a few words. The main development is reviewed from 1950 to now including: regulation, professional association roles, agreement and continuing education, development of clinical pharmacy, and updating of university training program. A new decree for the hospital pharmacist is in the course of being finalized, including new technologies: automated dispensing, automated compounding, centralization of sterile compounding, e-learning, traceability of medical devices and clinical pharmacy.